P. Beatty III (P47): the codex, its scribe, and its text - Malik, Peter (New Testament tools, studies and documents, 2017)
Since ancient works were preserved by means of handwritten copies, critical enquiry into their texts necessitates the study of such copies. In ?P.Beatty III (P47): The Codex, Its Scribe, and Its Text?, Peter Malik focuses on the earliest extensive copy of the Book of Revelation. Integrating matters of palaeography, codicology, and scribal practice with textual analysis, Malik sheds new light on this largely neglected, yet crucially important, early Christian papyrus. Notable contributions include a new proposed date for P47, identification of several previously unreported scribal corrections, as well as the discovery of the manuscript?s close affinity with the Sahidic version. Significantly, Malik?s detailed, data-rich analyses are accompanied by a fresh transcription and, for the first time, high-resolution colour photographs of the manuscript